CAEP Position Statement: Emergency department management of people with opioid use disorder. Issue 6 (November 2020) - Koh, Justin J.; Klaiman, Michelle; Miles, Isabelle; Cook, Jolene; Kumar, Thara; Sheikh, Hasan; Dong, Kathryn; Orkin, Aaron M.; Ali, Samina; Shouldice, Elizabeth
Abstract : Deaths due to opioid overdose have reached unprecedented levels in Canada; over 12, 800 opioid-related deaths occurred between January 2016 and March 2019, and overdose death rates increased by approximately 50% from 2016 to 2018. 1 In 2016, Health Canada declared the opioid epidemic a national public health crisis, 2 and life expectancy increases have halted in Canada for the first time in decades. 3 Children are not exempt from this crisis, and the Chief Public Health Officer of Canada has recently prioritized the prevention of problematic substance use among Canadian youth. 4